2012
DOI: 10.1016/j.ejpb.2011.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of differently formulated dry powder Newcastle disease vaccines for mass vaccination of poultry

Abstract: Dry powders containing a live-attenuated Newcastle disease vaccine (LZ58 strain) and intended for mass vaccination of poultry were prepared by spray drying using mannitol in combination with trehalose or inositol, polyvinylpyrrolidone (PVP) and/or bovine serum albumin (BSA) as stabilizers. These powders were evaluated for vaccine stabilizing capacity during production and storage (at 6ºC and 25ºC), moisture content, hygroscopicity and dry powder dispersibility. A mixture design, varying the ratio of mannitol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…It has been suggested (Huyge et al, 2012) that the ideal powder vaccine should meet the following requirements: (1) show no or only limited virus loss during production and storage; (2) be monodisperse; (3) consist of particles with a size that will enable exclusive targeting of the upper respiratory tract for primary vaccinations or the lower respiratory airways for secondary, booster vaccinations; (4) be easy to disperse into their primary particle size; (5) be non-hygroscopic to prevent hygroscopic growth of the vaccine virus-loaded particles in the airways during respiration (Morrow, 1986); and (6) be non-toxic for man, animals and the environment. In previous research Newcastle disease virus (NDV) powder vaccines based on mannitol and bovine serum albumin (BSA), which approximated to the requirements mentioned above, were prepared in a onestep spray-drying process (Corbanie et al, 2007;Huyge et al, 2012). A preliminary proof of principle experiment showed that the powder vaccine formulations induced high haemagglutination inhibiting (HI) antibody titres in 4-weekold broilers (Corbanie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested (Huyge et al, 2012) that the ideal powder vaccine should meet the following requirements: (1) show no or only limited virus loss during production and storage; (2) be monodisperse; (3) consist of particles with a size that will enable exclusive targeting of the upper respiratory tract for primary vaccinations or the lower respiratory airways for secondary, booster vaccinations; (4) be easy to disperse into their primary particle size; (5) be non-hygroscopic to prevent hygroscopic growth of the vaccine virus-loaded particles in the airways during respiration (Morrow, 1986); and (6) be non-toxic for man, animals and the environment. In previous research Newcastle disease virus (NDV) powder vaccines based on mannitol and bovine serum albumin (BSA), which approximated to the requirements mentioned above, were prepared in a onestep spray-drying process (Corbanie et al, 2007;Huyge et al, 2012). A preliminary proof of principle experiment showed that the powder vaccine formulations induced high haemagglutination inhibiting (HI) antibody titres in 4-weekold broilers (Corbanie et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown previously that vaccination of chickens with dispersed dry powder Newcastle disease virus vaccines can be used as an alternative for liquid spray or aerosol vaccination [19][20][21]. However, in those cases the vaccine consisted of a live attenuated vaccine as opposed to inactivated vaccine that was used here.…”
Section: Discussionmentioning
confidence: 93%
“…23 and 24) developed an HI titre of 4 log2, whereas the other animals developed a very low response (nr. 18,21) or no detectable response at all (nr. 16,17,19,20,22).…”
Section: Systemic Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…For example, UAVs could perform accurate fixed-point delivery of therapeutic drugs to treat animal infectious sources. They could also be used for targeted delivery of those vaccines that can be ingested or inhaled by animal populations [ 40 42 ]. In the event of disease outbreak or other disaster, UAVs could deliver therapeutic drugs and life-saving supplies to patients or isolated persons in remote areas.…”
Section: Potential and Challenges For Uav Use In Control Of Zoonosesmentioning
confidence: 99%